Improved Group Off-the-Record Messaging - Liu, Hong; Vasserman, Eugene Y.; Hopper, Nicholas (Association for Computing Machinery (ACM), 2013)
Off-the-Record Messaging (OTR) is an online analogy of face-to-face private chat { messages are confidential and au- thenticated at the time of the conversation, but cannot later be used to prove authorship. The original OTR protocol is limited to two parties, and is extended by multi-party OTR (mpOTR) to the group chat setting. In doing this, mpOTR unintentionally weakens the security properties provided by its two-party predecessor. We propose an improved group OTR (GOTR) protocol that provides unconditional repudi- ability, and show how to obtain data origin authentication given this level of repudiability. GOTR resists network failure, colluding and independent malicious insiders, and provides efficient and exible mem- bership management. We analyze the security properties and performance of GOTR, and present measurement re- sults of a proof-of-concept implementation of GOTR.
Keywords: Privacy; Repudiability; Group communication; Authentication; Robustness